APLIKASI KEUANGAN PADA CV.HENDEBRO - Megawati, Merti; Elzas, Elzas; Adriana, Windy; Mahendra, Iqbal (LP2M Universitas Nurdin Hamzah, 2024)
As a dynamic and leading company in the region, CV.Hendebro need to adopt information technology Innovation, especially through the implementation of website-based financial administration applications on CV.Hendebro is considered a proactive step to meet these demands. Trough a deep understanding of the needs and dynamics of the CV business. The system that will be built will only have admin page, no informationdisplayed on the landing page. On the admin page, you can process financial administration data such as incoming, outgoing transactions and financial reports. The system has two access rights, first admin and second owner. Admin can manage any data except deleting transactions. Leaders only view reports. Hendebro to increase efficiency in recording, monitoring and analyzing financial transactions, reducing the risk of manual errors.CV. Hendebro needs to overcome several main challenges in financial administration, including cash flow management, recordingtransactions, transparency of financial reports, and monitoring expenses. Implementation of applications on CV. Hendebro has had a significantpositive impact on the company's operational efficiency. This application helps speed up work processes, reduce human error, and increase dataaccuracy